Adenan government spends billions to address social problems - The, Star (The Star, 2014)
KUCHING: Social ills among teenagers must be addressed urgently to stop them from putting negative impact not only on society but also on the economy.On this, Incoming Chief Minister Tan Sri Adean Satem cited drug abuse as among the problems that proved costly to the government.